PENDAMPINGAN UMKM DUPA AJEG BALI DESA SAMBANGAN DALAM UPAYA MENINGKATKAN PEREKONOMIAN - Ni Nyoman Ayu Ningsih; Ketut Angga Asriani; Riana Dewi Kartika; Putu Eka Nopiyani (Bajang Institute, 2022)
Micro, small and medium enterprises (MSMEs) are one of the business fields that can develop and be consistent in the national economy. Micro, small and medium enterprises (MSMEs) are good forums for job creation designed by the government, private sector and individual business actors. One of them is the UKM internship program carried out by STIE Satya Dharma Singaraja students which aims to apply the knowledge gained during lectures in a more real world of work. SMEs are one of the potential for job expansion to overcome unemployment and poverty. These SMEs have an impact on every business run by the community in selling and promoting their products. This internship program is carried out for 1 month from August 1, 2022 - August 31, 2022. This internship activity takes place in the village of Sambangan at the Dupa UKM, namely Dupa Ajeg Bali, which in its distribution aims to increase income from the number of orders and at the same time increase public interest in buying incense. at Ajeg Bali. Emphasis on aspects under study include aspects of marketing and aspects of human resources using direct observation techniques to the location and seeing directly the marketing targets and the quality of their human resources. In this case, in terms of marketing, it can be concluded that to increase their income, Ajeg Bali employees must prioritize their promotions on social media. In addition, the most important thing is the presence of manpower. Good human resources are resources that are able to improve their companies and make innovations that make companies and organizations more recognized. For this reason, in terms of human resources or labor, they must cooperate more to meet customer satisfaction both in terms of printing and packaging of incense.